Factors affecting job stress among executive employees at a GLC - Norzarafina, Abdul Malek (2019)
Currently, one of the most serious situations handled by employees is job stress. Stress has been remarked as a cutting-edge the world’s disease that develops in various forms in place of work. Stress is an effect of damaging psychological and physical harms that that develop in someone as the effect of failing to adapt to the demand that way beyond the expectation. This study wants to determine whether job satisfaction, workload, role conflict and reward and recognition influence job stress. Data was obtained from 130 employees in Penang, Malaysia. The result were analyzed with Statistical Package for the Social Sciences (SPSS) version 24 indicate negative relationship of job stress with job satisfaction, no correlation of job stress with reward and recognition and positive relationship between workload and role conflict with job stress. The result also showed workload, role conflict and reward and recognition have significant impact on job stress but not job satisfaction. This study contributes to the understanding of factors influencing job stress among employees in the one of the GLC (Government Linked Companies) in Malaysia